Study of the surrogate ratio method by determination of 56Fe(n,xp) cross sections - Aman Sharma; Punit Dubey; Utkarsha Mishra; Nitin Dubey; Jyoti Pandey; Ramandeep Gandhi; A. Pal; Abhijit Baishya; T. Santhosh; P.C. Rout; B.K. Nayak; S. Santra; et al. (Physics Letters B, 2024)
In recent years (n,xp) cross sections of some long-lived radionuclei which are of importance in the upcoming fusion reactor technologies have been constrained using the surrogate ratio method. But the (n,xp) cross sections for the stable nuclei for which a great wealth of data is available from the direct measurements have not been constrained using surrogate ratio method yet, so that the consistency of the surrogate ratio method can be checked. In this study we have investigated the validity of surrogate ratio method by constraining 56Fe(n,xp) cross sections and then the results are compared with the available experimental data, evaluated data and the statistical model predictions. In this study 52Cr(n,xp) reaction has been used as the reference reaction in the surrogate ratio method. It is found in this study that (n,xp) cross sections constrained using surrogate ratio method are sensitive to the spin distribution of the compound nuclei populated in the surrogate reactions. It is also presented in this study that the proton emission probabilities for 57Fe and 53Cr are highly spin dependent. It is concluded that the surrogate ratio method is not suitable for constraining the (n,xp) cross sections.